Haemodynamic outcomes following aortic valve-in-valve procedure. Issue 2 (9th July 2018) - Zenses, Anne-Sophie; Dahou, Abdellaziz; Salaun, Erwan; Clavel, Marie-Annick; Rodés-Cabau, Josep; Ong, Géraldine; Guzzetti, Ezéquiel; Côté, Mélanie; De Larochellière, Robert; Paradis, Jean-Michel; Doyle, Daniel; Mohammadi, Siamak; et al.
Abstract : Background and objectives: Transcatheter aortic valve-in-valve implantation (ViV) has emerged as a valuable technique to treat failed surgical bioprostheses (BPs) in patients with high risk for redo surgical aortic valve replacement (SAVR). Small BP size (≤21 mm), stenotic pattern of degeneration and pre-existing prosthesis–patient mismatch (PPM) have been associated with worse clinical outcomes after ViV. However, no study has evaluated the actual haemodynamic benefit associated with ViV. This study aims to compare haemodynamic status observed at post-ViV, pre-ViV and early after initial SAVR and to determine the factors associated with worse haemodynamic outcomes following ViV, including the rates of high residual gradient and 'haemodynamic futility'. Methods: Early post-SAVR, pre-ViV and post-ViV echocardiographic data of 79 consecutive patients who underwent aortic ViV at our institution were retrospectively analysed. The primary study endpoint was suboptimal valve haemodynamics (SVH) following ViV defined by the Valve Academic Research Consortium 2 as the presence of high residual aortic mean gradient (≥20 mm Hg) and/or at least moderate aortic regurgitation (AR). Haemodynamic futility of ViV was defined as <10 mm Hg decrease in mean aortic gradient and no improvement in AR compared with pre-ViV. Results: SVH was found in 61% of patients (57% high residual gradient, 4% moderate AR) after ViV versus 24% early after SAVR. Pre-existing PPM and BP mode of failure by stenosis were independently associated with the primary endpoint (OR: 2.87; 95% CI 1.08 to 7.65; p=0.035 and OR: 3.02; 95% CI 1.08 to 8.42; p=0.035, respectively) and with the presence of high residual gradient (OR: 4.38; 95% CI 1.55 to 12.37; p=0.005 and OR: 5.37; 95% CI 1.77 to 16.30; p=0.003, respectively) following ViV. Criteria of ViV haemodynamic futility were met in 7.6% overall and more frequently in patients with pre-existing PPM and stenotic BP (18.5%) compared with other patients (2.0%). ViV restored haemodynamic function to early post-SAVR level in only 34% of patients. Conclusion: Although ViV was associated with significant haemodynamic improvement compared with pre-ViV in >90% of patients, more than half harboured SVH outcome. Furthermore, only one-third of patients had a restoration of valve haemodynamic function to the early post-SAVR level. Pre-existing PPM and stenosis pattern of BP degeneration were the main factors associated with SVH and haemodynamic futility following ViV. These findings provide strong support for the prevention of PPM at the time of initial SAVR and careful preprocedural patient screening.